Deaf primary school children’s achievement in mathematics - Gottardis, L (2016)
The present research aims to evaluate the extent of deaf children’s delay in mathematics, identifying the moderators of this delay and determine the longitudinal predictors of their mathematical achievement. For five decades, studies have reported that deaf children lag behind their hearing peers in mathematics (Gottardis, Nunes and Lunt, 2011). Background factors such as age, degree of hearing loss, presence of cochlear implant and types of educational provision were previously hypothesised to be moderators of the extent of this delay but, up to now, they have not been tested. Pagliaro (2010) argued that number knowledge, working memory and degree of hearing loss could be possible causes of deaf children’s difficulties in mathematics but no clear conclusions were reached. The present investigation aims to provide insight into the causes of deaf children’s delay in mathematics. The survey study addressed the first aim of the present study. The maths test of the Performance Indicators for Primary School (PIPS) was used as outcome measure. Factors related to deaf children (degree of hearing loss, age, years in education, presence of cochlear implant, gender, causes of deafness) and background factors (highest maternal education, language used at home, type of educational provision) were assessed as possible predictors and moderators of the extent of deaf children’s delay in mathematics. The overall extent of deaf children’s delay in mathematics was of -1.76 SDs. The older the children get and the more years they spend in special schools for the deaf or in units for hearing impaired, the wider is their gap in mathematics achievement compared with their hearing peers. It is, therefore, necessary to intervene in their mathematical learning in the early years of schooling in order to create pathways for improvement. The second aim of the present study was addressed through a longitudinal design. Logical-mathematical reasoning, working memory and counting ability were chosen as predictors of deaf children’s mathematical attainment on the basis of theoretical framework, evidence from longitudinal studies and from the analysis of the difficulties that deaf children have in these factors compared with hearing peers. Hierarchical regression analyses were used to assess the independence of the contributions of logical-mathematical reasoning, working memory and counting ability to the prediction of deaf children’s mathematical achievement measured through the PIPS. Age, years in education, type of educational provision and non-verbal intelligence were used as controls. Counting ability and working memory did make independent contributions to the prediction of deaf children’s mathematical success but logical mathematical reasoning was by far the strongest predictor. When the predictors were entered in the model, none of the control variables predicted significantly deaf children’s mathematical achievement. This study makes several empirical contributions. First, it established age, years in education and types of educational provision as moderators of the extent of deaf children’s delay in mathematics. Second, it determined the plausibility of a causal link between logical-mathematical reasoning, counting ability, working memory and deaf children’s mathematical achievement. The implication is that schools must explicitly plan to improve deaf children’s mathematical reasoning, counting ability and working memory when they are in kindergarten and in the first years of school in order to help the children’s mathematical development.